2016
DOI: 10.1016/j.cbpa.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient regulation of gene expression by O-GlcNAcylation of chromatin

Abstract: O-GlcNAcylation is a dynamic post-translational modification that is responsive to nutrient availably via the hexosamine biosynthetic pathway and its endproduct UDP-GlcNAc. O-GlcNAcylation serves as a nutrient sensor to regulate the activities of many proteins involved in nearly all biological processes. Within the last decade, OGT, OGA and O-GlcNAcylation have been shown to be at the nexus of epigenetic marks controlling gene expression during embryonic development, cell differentiation, in the maintenance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…More recently, in a double-bind, randomized cross-over trial in menopausal women isoflavones affected in peripheral blood mononuclear cells the expression of 357 genes which are involved in inflammation, oxidative phosphorylation and cell cycle have been published up to now describing the genomic impact of polyphenols and polyphenol-rich foods in humans. It has been observed that the daily intake of 150 mg quercetin for 2 weeks significantly affected the expression of 788 genes in CD14-positivemonocytes, genes related to immune system, apoptosis or cell signaling pathways [16].…”
Section: Epigenetic Effects Of Bioactive Compounds Micro and Macronumentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, in a double-bind, randomized cross-over trial in menopausal women isoflavones affected in peripheral blood mononuclear cells the expression of 357 genes which are involved in inflammation, oxidative phosphorylation and cell cycle have been published up to now describing the genomic impact of polyphenols and polyphenol-rich foods in humans. It has been observed that the daily intake of 150 mg quercetin for 2 weeks significantly affected the expression of 788 genes in CD14-positivemonocytes, genes related to immune system, apoptosis or cell signaling pathways [16].…”
Section: Epigenetic Effects Of Bioactive Compounds Micro and Macronumentioning
confidence: 99%
“…This potential cardiovascular health benefit is in agreement with a recent study that showed an association between the intake of flavanols and reduced risk of coronary heart diseases. However, comprehensive understanding of the biological activity of flavanols including their mechanisms of action in humans is still enigmatic [16]. The gene expression profile of blood leukocytes was obtained following 8 weeks consumption of MOF.…”
Section: Nutrigenomic Analysis Of Transcriptional Effects Of Mofmentioning
confidence: 99%
See 2 more Smart Citations
“…O‐GlcNAc adducts are also present on histone proteins indicating OGT contributes to modulate epigenetic regulatory landscapes . OGT interacts with other chromatin modification proteins and transcriptional regulators, like TET proteins (mediate the 5 hydroxy‐methylation of cytosines, 5hmC), HCF1 (promotes histone H3 lysine 4 trimethylation, H3K4me3), MLL5 (catalyses H3K4 mono‐and di‐methylation, H3K4me1/2) and Polycomb proteins (contribute to H2BK119 ubiquitination and H3K27 trimethlyation, H3K27me3) . Finally, transcription factors themselves can be modified by OGT.…”
mentioning
confidence: 99%